2012
DOI: 10.1089/jmf.2012.2275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Sulfur-Containing Compounds from Garlic

Abstract: We identified four anti-inflammatory sulfur-containing compounds from garlic, and their chemical structures were identified as Z-and E-ajoene and oxidized sulfonyl derivatives of ajoene. The sulfur compounds inhibited the production of nitric oxide (NO) and prostaglandin E2 (PGE2) and the expression of the pro-inflammatory cytokines tumor necrosis factora, interleukin-1b, and interleukin-6 in lipopolysaccharide (LPS)-activated macrophages. Western blotting and reverse transcription-polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 44 publications
2
85
0
4
Order By: Relevance
“…suggested that the aqueous ethanolic C. nutans extract that successfully isolated sulphur‐containing compounds (clinamide A, B, and C, 2‐ cis ‐entadamide A, and entadamide A and C) contained anti‐inflammatory properties based on superoxide anion production and an elastase release assessment. Additionally, Allium sativum or commonly known as garlic, has a long history of use worldwide for its culinary and therapeutic properties, such as anticancer, antioxidant and anti‐inflammation activities . The therapeutic function of garlic was well known to be dominated by its rich sulphur‐containing compounds and organosulphur content.…”
Section: Resultsmentioning
confidence: 99%
“…suggested that the aqueous ethanolic C. nutans extract that successfully isolated sulphur‐containing compounds (clinamide A, B, and C, 2‐ cis ‐entadamide A, and entadamide A and C) contained anti‐inflammatory properties based on superoxide anion production and an elastase release assessment. Additionally, Allium sativum or commonly known as garlic, has a long history of use worldwide for its culinary and therapeutic properties, such as anticancer, antioxidant and anti‐inflammation activities . The therapeutic function of garlic was well known to be dominated by its rich sulphur‐containing compounds and organosulphur content.…”
Section: Resultsmentioning
confidence: 99%
“…This same group also found that DADS and allicin at 100 μM reduced LPS‐induced TNF‐α levels (Keiss et al ., ). More recently, using RAW264.7 cells, Lee et al () showed that ajoene extracted from garlic inhibited the expression of TNF‐α mRNA (Lee et al ., ), and You et al () reported that diallyl trisulphide (DATS, 100 μM) inhibited several cytokines including TNF‐α (You et al ., ). Using RAW264.7 macrophages, Shin et al () found that raw garlic extracts decreased LPS (1 µg/mL)‐induced TNF‐α secretion but that allicin (1 µg/mL) had no effect on the production of this cytokine by LPS (Shin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 46 have studied the anti-inflammatory activity of four garlic constituents, i.e., Z-and Eajoene and oxidized sulfonyl derivatives of ajoene. According to their study, the sulfur compounds inhibited the production of nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) and the expression of the pro-inflammatory cytokines tumor necrosis factor-α, interleukin-1β, and interleukin-6 in LPSactivated macrophages.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%